Kinetic modeling of liquid phase autoxidation of cumene - Bhattacharya, Arijit (Chemical Engineering Journal, 2008)
A new kinetic model for the liquid phase autoxidation of cumene has been developed utilizing the existing knowledge about the traditional free-radical mechanism involving the initiation of the free-radicals, the chain propagation and transfer and the various modes of radical termination. Unlike previous work, in the re-organized reaction network an important cross-termination step replaces an often used but less likely one and a new derivation of the rate model has been provided. A base set of rate parameters for the elementary steps within this reaction network were chosen, many of them were same or very similar to those published in the literature, with a few critical ones re-estimated for correct match with directly observed kinetic data reported in the literature on cumene oxidation in bench scale reactors. Embedding this kinetic sub-model within a simple reaction engineering model for a single air-sparged continuous cumene oxidator, the liquid oxidate composition at the reactor exit could be predicted that compared closely with some limited published data from an industrial reactor. It is hoped that the kinetic model presented here would be a useful tool in the analysis and design of other autoxidation reactors as well with minor adaptations. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: air-sparged continuous oxidator; cumene oxidation; free-radical mechanism; kinetic model; liquid phase autoxidation